VD_FINDINFO HC / 2016 / 80 vom 22. Oktober 2015 - VD Tribunal cantonal (2015)
RÉSILIATION ABUSIVE, RÉSILIATION IMMÉDIATE, TREIZIÈME SALAIRE, SALAIRE, JUSTE MOTIF, MALADIE | 324 CC, 324a al. 4 CO, 324a CO, 336c CO, 337 al. 1 CO, 337 al. 2 CO, 337 al. 3 CO, 337 CO